A Study on Size and Duration of Training Programmes - Vikram Singh; Lakshmi Murthy (Journal of Agricultural Extension Management, 2025)
Training has long been recognized as an important component of most development activities. Training can help improve awareness, bring about change in knowledge, attitude, behavior and skill s of the trainees which they can transfer to their jobs and thus contribute professionally. Training is a way of providing information and direction in a planned and structured manner to employees or customers or clients on how to accomplish specific tasks related to organizational needs and objectives